1996
DOI: 10.1007/s002689900130
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival of Patients with Papillary Thyroid Cancer after Surgical Microdissection

Abstract: A total of 195 patients had surgery for papillary thyroid cancer. The mean age at operation was 50 years. A microdissection technique was used for total thyroidectomy and lymph node clearance. Postoperative radioiodine tests showed no uptake or an uptake close to the background activity in 77% of the examined patients. By counting the lymph nodes removed at surgery we were able to check on the quality of the lymph node dissection. Men had a higher incidence (70%) of lymph node metastases than women (45%). Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
1
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(144 citation statements)
references
References 23 publications
4
133
1
6
Order By: Relevance
“…Patients with PTC have excellent prognosis; however, the presence of LNM significantly increases the risk of locoregional recurrence, and some groups have demonstrated decreased disease‐free survival rate and increased mortality associated with regional LNM 4, 5, 6, 7, 8, 9, 10. Extensive LND has the potential to decrease regional recurrence and increase disease‐free survival, but may lead to clinically important postoperative morbidities 13, 14, 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PTC have excellent prognosis; however, the presence of LNM significantly increases the risk of locoregional recurrence, and some groups have demonstrated decreased disease‐free survival rate and increased mortality associated with regional LNM 4, 5, 6, 7, 8, 9, 10. Extensive LND has the potential to decrease regional recurrence and increase disease‐free survival, but may lead to clinically important postoperative morbidities 13, 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical LNM in PTC have been identified as an independent risk factor for regional recurrence 4, 5, 6, 7, and emerging evidences from large population‐based studies have indicated decreased disease‐free survival rate and increased mortality associated with regional LNM 7, 8, 9, 10. There is universal agreement that therapeutic lateral neck dissection (LND) should be undertaken in patients with PTC and clinically lateral LNM (LLNM) on the basis of palpation or imaging examination 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Regional lymph node metastases are present at the time of diagnosis in 20%-90% of patients with papillary carcinoma and a lesser proportion of patients with other histotypes (75,102). In many cases, these lymph nodes do not appear abnormal to inspection (103). Bilateral central (compartment VI) node dissection may improve survival (compared to historic controls) and reduce the risk for nodal recurrence (76,103).…”
Section: What Is the Appropriate Operation For Differentiated Thyroidmentioning
confidence: 99%
“…In many cases, these lymph nodes do not appear abnormal to inspection (103). Bilateral central (compartment VI) node dissection may improve survival (compared to historic controls) and reduce the risk for nodal recurrence (76,103). This central compartment dissection can be achieved with low morbidity in experienced hands (104)(105)(106)(107).…”
Section: What Is the Appropriate Operation For Differentiated Thyroidmentioning
confidence: 99%
“…The complication's rate we reported, in term of temporary and permanent hypoparathyroidism and inferior laringeal nerve palsy, might be considered acceptable in a referral centre for thyroid surgery compared to those presented in the main experiences reported in literature, especially when considering the higher risk of complications if reoperation is required (up to 9% of laryngeal nerves injury and 14% of hypoparathyroidism) (22)(23)(24)(25)(26)(27)(28). We report a recurrence rate in RAI treated patients of 3.2%, in not treated of 4.3%, with not significant difference.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 84%